The Mediating Effect of Organizational Culture on the Relationship Between Organizational Commitment and Work-life Balance Among Business Management Faculty - Sabuero, Jimmy B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Work-life balance involves work and family. Work's great obligations require time for friends, family, civic activity, personal growth, self-care, and other personal pursuits. This study aimed to determine the mediating effect of organizational culture on the relationship between organizational commitment and work-life balance among business management faculty. This study used a descriptive correlational research design with mediation analysis. Stratified Random sampling was used with a total sample size of 130 respondents. Data were analyzed through descriptive and inferential statistics using mean and standard deviation. The inferential statistics, Pearson R was used to test the significant relationship, while mediation analysis was used to determine the effect of organizational culture on the relationship between organizational commitment and work-life balance. The findings reveal that the overall mean of faculty’s organizational commitment is (X̄=3.34, SD=0.59), interpreted as "Very high commitment". The study revealed that the overall mean work-life balance of the respondents is (X̄=3.42, SD=0.72), interpreted as a "Very high work-life balance." While the overall mean of faculty's organizational culture is (X̄=3.41, SD=0.51) interpreted “Very high organizational culture". The study showed a significant relationship between work-life balance and organizational commitment (r=0.785; p=.00), in which faculty who have high organizational commitment tend to have high work-life balance. The study also showed that there is a significant relationship between organizational culture and organizational commitment (r=0.716; p=.00) in which faculty who rated high organizational culture tend to have high organizational commitment. Moreover, there is a significant relationship between organizational culture and Work-life balance (r=.582; p=.00), of which faculty who have rated high organizational culture tend to have high work-life balance. However, organizational culture does not significantly mediate the relationship between organizational commitment and work-life balance among business management faculty. Thus, it rejected the null hypothesis. It can be concluded that commitment serves as a driving force in all organizational and institutional dealings. Faculty with a high organizational commitment tend to have high ratings on their measure of work-life balance. The Spillover Theory of Wilensky also proved in this study that Work-life Balance can impact one's emotions, motivation, and behavior in another area, leading to a ripple effect or spillover.